Exploring the Role of PET-CT in Radiotherapy Planning: Insights from Clinical Experience (Bangladesh Journal of Nuclear Medicine, 2025)
Radiotherapy is a cornerstone of cancer treatment, benefiting nearly 50% of patients during their disease journey. Despite its efficacy, traditional imaging modalities like contrast-enhanced computed tomography (CT) face limitations in accurately delineating tumors and identifying metastatic spread, which is crucial for effective radiotherapy planning. This study explores the impact of integrating Positron Emission Tomography and Computed Tomography (PET-CT) in radiotherapy planning compared to CT alone, particularly in resource-limited settings like Bangladesh. PET-CT, by providing molecular-level insights through tracers such as 2-fluoro-2-deoxyglucose (18F-FDG), offers superior tumor visualization and metabolic assessment. Two case studies highlight the clinical significance of PET-CT-based planning in radiotherapy. In the case of non-small cell lung cancer (NSCLC), PET-CT revealed previously undetected metastases, prompting a shift from radiotherapy to systemic chemotherapy, thus avoiding inappropriate treatment. In another case involving male breast carcinoma, PET-CT resolved uncertainties in tumor localization, enabling precise delineation and dose adjustments for effective radiotherapy. Both cases underscore PET-CT’s ability to refine treatment strategies, enhance diagnostic accuracy, and improve therapeutic outcomes. While CT remains widely accessible, its limitations highlight the need for complementary imaging. PET-CT bridges this gap, improving tumor staging, delineation, and treatment adaptation. However, challenges such as cost and accessibility hinder its widespread adoption in resource-constrained regions. This study emphasizes the transformative potential of PET-CT in radiotherapy workflows, advocating for its integration to enhance treatment precision and optimize oncological care in low-resource settings.Bangladesh J. Nuclear Med. 27(2): 267-272, 2024